Genetic dissection of mechanosensory transduction: mechanoreception-defective mutants of Drosophila. - Kernan, M.; Cowan, D.; Zuker, C.S. (Neuron, 1994)
To identify genes involved in mechanotransduction, Drosophila larvae were screened for X-linked mutations affecting a behavioral response to touch. Many mutations that caused nondevelopmental defects were recovered, among them multiple alleles of the genes uncoordinated (unc) and uncoordinated-like (uncl). Adult flies mutant in these genes showed reduced viability that was associated with behavioral phenotypes ranging from reduced locomotor activity to total uncoordination. Behavioral analysis of mosaic flies indicated that external sensory bristles are a focus of the unc mutant defect. Extracellular recordings from mutant mechanosensory bristles revealed that mechanoreceptor potentials were absent or reduced in both unc and uncl mutants. A second genetic screen, for unc-like uncoordination, yielded mutations in seven genes on the second chromosome; mutations in five of these genes also reduced or eliminated bristle mechanoreceptor potentials. These mutants provide the basis for a genetic, electrophysiological, and molecular dissection of mechanotransduction.